Gargantua (Jr!) : defender of Earth - Sylvester, Kevin (Groundwood Books/House of Anansi Press, 2019)
"Gargantua Jr. wants to grow up to be just like his mom. Before he was born, Mom had a reputation for being a little wild - she wreaked havoc everywhere she went with her monster strength and fiery flames. But now she prefers to repair some of the damage, and she only knocks over buildings that are supposed to come down. She also protects Earth from dangerous space robots and giant asteroids. Gargantua Jr. would like to help out, but Mom says he's too little. So he sets out to show her that he's not a baby anymore ... Thankfully, Mom comes to the rescue just in time."--Amazon.